Antioxidant and immunostimulatory effect of potential probiotic Lactobacillus paraplantarum SC61 isolated from Korean traditional fermented food, jangajji. (December 2018) - Son, Sung-Ho; Yang, Seo-Jin; Jeon, Hye-Lin; Yu, Hyung-Seok; Lee, Na-Kyoung; Park, Young-Seo; Paik, Hyun-Dong
Abstract: This study aimed to isolate and demonstrate their antioxidant and immunostimulatory activities of potential probiotics. The isolated strains, S. Pum19, SC28, and SC61 showed potential probiotic properties including stability in artificial gastric and bile conditions, non-production of β-glucuronidase, suitable antibiotic susceptibility, and attachment to intestinal cells. S. Pum19, SC28, and SC61 strains were identified as Leuconostoc citreum, Pediococcus pentosaceus, and Lactobacillus paraplantarum, respectively. Of the 3 potential probiotic LAB strains, intact cells of L . paraplantarum SC61 showed higher antioxidant activity, including DPPH radical scavenging, β-carotene bleaching inhibition, reducing power, superoxide anion scavenging, and ABTS radical scavenging activity. In addition, L . paraplantarum SC61 produced the most nitric oxide production and its mRNA expression level for iNOS, IL-1β, IL-6, and TNF-α were superior to those of L . rhamnosus GG. Therefore, L. paraplantarum SC61 was demonstrated to exhibit antioxidant and immunostimulatory activity and to have potential use as a probiotic product. Highlights: Lactobacillus paraplantarum SC61 was isolated from jangajji under harsh conditions. L. paraplantarum SC61 showed high efficacy, safety, and stability. L. paraplantarum SC61 showed high antioxidant and immune-enhancing activity. L. paraplantarum SC61 could be used as a probiotic.